2019
DOI: 10.1002/cmdc.201900376
|View full text |Cite
|
Sign up to set email alerts
|

Second‐Generation Inhibitors of the Mitochondrial Permeability Transition Pore with Improved Plasma Stability

Abstract: Excessive mitochondrial matrix Ca2+ and oxidative stress leads to the opening of a high‐conductance channel of the inner mitochondrial membrane referred to as the mitochondrial permeability transition pore (mtPTP). Because mtPTP opening can lead to cell death under diverse pathophysiological conditions, inhibitors of mtPTP are potential therapeutics for various human diseases. High throughput screening efforts led to the identification of a 3‐carboxamide‐5‐phenol‐isoxazole compounds as mtPTP inhibitors. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…MPTP is an important channel protein across the mitochondrial inner and outer membranes (29)(30)(31). Previous studies have identified that MPTP opening is a key step to induce cell mitochondrial damage and activates the mitochondrial apoptotic pathway (32)(33)(34). The present study revealed that extracellular acidosis increased MPTP opening, while the overexpression of TRAP1 reversed this effect.…”
Section: Discussionsupporting
confidence: 54%
“…MPTP is an important channel protein across the mitochondrial inner and outer membranes (29)(30)(31). Previous studies have identified that MPTP opening is a key step to induce cell mitochondrial damage and activates the mitochondrial apoptotic pathway (32)(33)(34). The present study revealed that extracellular acidosis increased MPTP opening, while the overexpression of TRAP1 reversed this effect.…”
Section: Discussionsupporting
confidence: 54%
“…Several compounds have been identified which appear to directly inhibit the MPTP through its (putative) components [ [34] , [35] , [36] ]. Since they act as repressors, they may be more useful in other contexts in which the MPTP plays a role, e.g.…”
Section: Mitochondrial Ion Channels and Their Pharmacological Targeting By Small Moleculesmentioning
confidence: 99%
“…The further exploration of potent and selective cyclophilin D-independent MPTP inhibitors performed by screening the small-molecule libraries identified an isoxazole compound that possessed the inhibitory activity for MPTP [ 81 ]. Further optimization work was focused on improving the pharmacokinetic properties of the identified compound, resulting in a second-generation MPTP inhibitor with improved plasma stability—TR001 [ 82 ]. Animal studies using the zebrafish model of DMD and myoblasts and myotubes from DMD patients proved the efficiency of TR001 in the restoration of mitochondrial dysfunction regulated by MPTP [ 83 ].…”
Section: Mitochondrial Dysfunction In Specific Neuromuscular Disordersmentioning
confidence: 99%